AVALIAÇÃO DA RESISTÊNCIA À TRAÇÃO DA UNIÃO DE LIGAS DE NI-CR E CO-CR ATRAVÉS DE SOLDAGEM A LASER E PLASMA, E SEUS GRUPOS CONTROLE EM MONOBLOCO - Lustosa, Diogo Belas (2009)
Problem determination: the use of welding often is required in the manufacture of prosthetic infrastructures in Implantology. Choosing the best method usually falls to the laser welding. However, the high cost of equipment can prevent the use of this welding method. Proposition: This study evaluated the tensile strength of the union of Ni-Cr alloys (Wiron-99 US) and Co-Cr (CNG - Brazil) used in prosthetic implantology joined by two welding methods (welding TIG and laser welding), and compared the possibility to use different methods for welding the alloys used. Materials and methods: were made ten proof bodies in one piece and ten pairs of half of these proof bodies for welding for each metal alloy (Ni-Cr and Co-Cr). In total, 100 proof bodies in acrylic resin were cast by the lost wax technique. These halves were joined together in equal quantity by laser welding and plasma. Such structures with the control group (monobloc) were subjected to tensile strength test. The highest averages were in the control group of Ni-Cr alloy, then the control group of Co-Cr alloy, TIG Co-Cr alloy and Ni-Cr laser. TIG groups C0-Cr alloy, and laser alloys Ni-Cr and Co-Cr had similar statistical behavior even though they have different results. Results: the highest average tensile strenght were the control groups (monoblock) for both Ni-Cr alloy as for the Co-Cr (p <0,001). TIG welding presented higher average compared to the laser welding for the Ni-Cr alloy (P <0.001). For the Co-Cr alloy, the laser group had higher average compared with the TIG welding, however this difference was not statistically significant (P> 0.001). Conclusions: all groups had higher rupture values than maximum occlusal loads encountered in the literature, both the average for each group and for each body-ofproof rated